2015
DOI: 10.11138/mltj/2015.5.3.187
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of body mass status with running and jumping performances in young basketball players

Abstract: IntroductionThe research on the physical determinants of basketball performance from a physiological perspective has focused on profiling of physical fitness characteristics of elite players [1][2][3][4][5][6] . It has been suggested that elite basketball players should have high stature and increased anaerobic power 7,8 . Moreover, the achievement of an optimal body mass (BM) is a main concern in daily basketball practice. Body mass index (BMI) is an easily-administered and inexpensive tool to monitor BM stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
15
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 36 publications
5
15
2
Order By: Relevance
“…Basketball is one of the most popular team sports in Europe and performance in this sport depends on a variety of physical, physiological, psychological and technical characteristics [1][2][3][4][5]. Accuracy in shooting is a technical characteristic that discriminates basketball players by competition level [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Basketball is one of the most popular team sports in Europe and performance in this sport depends on a variety of physical, physiological, psychological and technical characteristics [1][2][3][4][5]. Accuracy in shooting is a technical characteristic that discriminates basketball players by competition level [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of vertical jumping is particularly emphasized because the game is oriented around a basket that is set at a top height of 3.05 m. Players who have superior jumping capabilities are able to outperform their opponents in numerous situations requiring offensive and defensive responsibilities, such as blocking, jump shooting, and rebounding [ 6 , 7 ]. Consequently, athletes and coaches in this sport are highly interested in testing and developing vertical jumping ability [ 8 – 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Evidently, little is known about the validity of other jumping performances (i.e. running jumps, reactive jumps) and their applicability in differentiating between playing levels and between playing positions [ 7 , 8 , 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, regular participation of students in a sport activity might help increase PA levels and decrease body mass and body fat percentage (BF). However, a series of recent studies on the prevalence of excess body weight and obesity in various sport and age groups has revealed similar rates between athletes and non-athletes (Nikolaïdis 2012 ; Nikolaidis et al 2015 ). The above-mentioned studies clearly indicated that regular participation in a sport per se does not result in low rates of body mass and BF, and identified the need for further research in markers of excess body weight and obesity in sport groups.…”
Section: Introductionmentioning
confidence: 99%